Two-component developer

By using a two-component developer containing silicone particles treated with silicone oil and fatty acid metal salt particles in the printing equipment, and forming a crystalline polyester resin coating on the carrier, the problem of charge unstable in different humidity environments is solved, and stable image output and equipment life are achieved.

JP2025014396APending Publication Date: 2025-01-30SHARP KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023116914
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

In the prior art, when silicone particles treated with silicone oil are used as external agents, moisture adsorption in low-humidity environments leads to unstable charge, resulting in printing quality problems, such as uneven image output and charge leakage, and increased moisture adsorption in high-humidity environments leads to charge leakage and image blur.

Method used

A two-component developer containing silicone particles treated with silica gel oil and fatty acid metal salt particles is used, wherein the free oil amount of the silica gel particles is less than 3%, and a crystalline polyester resin coating is formed on the carrier, combined with an appropriate heat treatment process to adjust the compatibility and adhesion of the resin and control the surface exposed area of ​​the carrier.

Benefits of technology

It can effectively stabilize charge in low-humidity and high-humidity environments, reduce image output unevenness and charge leakage, improve print quality, and extend the service life of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025014396000001_ABST
    Figure 2025014396000001_ABST
Patent Text Reader

Abstract

To provide a two-component developer that maintains a good charge rising property through its product life in both a low humidity environment and a high humidity environment.SOLUTION: A two-component developer of the present disclosure contains a toner in which an external additive is attached to a surface of a toner particle, and a carrier. The toner particle includes an amorphous polyester resin and a crystalline polyester resin. The external additive includes fatty acid metal salt particles, and silica particles surface-treated with silicone oil. An amount of free oil in the silica particles is 3% or more and 6% or less. A particle diameter of the fatty acid metal salt particles is 0.5 μm or more and 1.5 μm or less. The carrier includes a ferrite core material, and a straight silicone resin coating layer formed on at least part of a surface of the ferrite core material.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to two-component developers. [Background technology]

[0002] As a developer used in image forming devices such as electrophotographic copying machines, multifunction machines, printers, and facsimile machines, two-component developers containing a toner having an external additive attached to the surface of the toner particles (toner core) and a carrier are widely used.

[0003] A known toner uses silica particles that have been surface-treated with silicone oil (silica particles that have been surface-treated with polydimethylsiloxane (PDMS)) as an external additive. The use of silica particles that have been surface-treated with silicone oil as an external additive provides many benefits, such as improved charging properties and toner mixing properties (ease of mixing) when replenishment.

[0004] As an example of a toner using silica particles surface-treated with silicone oil, Patent Document 1 discloses a toner having toner particles, fatty acid metal salt particles, and silica particles, in which the silica particles have been surface-treated with at least one of alkoxysilane and alkoxysilazane, and with silicone oil. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2011-47988 A Summary of the Invention [Problem to be solved by the invention]

[0006] It is not clear why the use of silica particles surface-treated with silicone oil as an external additive results in good electrostatic properties, but it is believed that the parts that have been surface-treated with the oil have the property of easily absorbing moisture, and the oil parts that absorb moisture from the air become a conductive path for charges, thereby improving electrostatic properties in low-humidity environments.

[0007] However, even if silica particles surface-treated with silicone oil are used as an external additive, there is a problem that toner charge-up cannot be suppressed under conditions where image output continues with low printing (a state in which the ratio of the area of ​​the printed image to the area of ​​the entire recording medium) in a low humidity environment. In addition, there is a problem that the mixing property at the time of toner replenishment deteriorates, and fogging is likely to occur. Note that fogging refers to a phenomenon in which low-charge toner is developed in non-image areas where toner is not originally developed (a phenomenon in which low-charge toner adheres to the photosensitive drum).

[0008] In addition, when the toner is left in a high humidity environment for a long period of time, the amount of moisture adsorbed by the silica particles surface-treated with silicone oil increases, and the moisture adheres to the carrier surface, which excessively promotes charge leakage and causes charging failure, which in turn causes problems such as fogging.

[0009] The contents of the present disclosure have been discovered in consideration of such circumstances, and a primary object of the present disclosure is to provide a two-component developer that exhibits good charge rise throughout its product life in both low-humidity and high-humidity environments. [Means for solving the problem]

[0010] In order to solve the above problems, the two-component developer disclosed herein is a two-component developer containing a toner having an external additive attached to the surface of the toner particles and a carrier, the toner particles contain an amorphous polyester resin and a crystalline polyester resin, the external additive contains fatty acid metal salt particles and silica particles surface-treated with silicone oil, the free oil content of the silica particles is 3% or more and 6% or less, the particle diameter of the fatty acid metal salt particles is 0.5 μm or more and 1.5 μm or less, and the carrier is a ferrite core material having a straight silicone resin coating layer formed on at least a part of the surface. In the following, the "silica particles surface-treated with silicone oil" are also referred to as "oil-treated silica particles".

[0011] In the above two-component developer, in differential scanning calorimetry of the toner, the amount of heat absorbed from the crystalline polyester resin in the 1st run in which the toner is heated from 30°C to 150°C at a heating rate of 10°C per minute is defined as E1, and the amount of heat absorbed from the crystalline polyester resin in the 2nd run in which the toner is cooled to 30°C at a cooling rate of 10°C per minute after the 1st run and held for 1 minute, and then heated again from 30°C to 150°C at a heating rate of 10°C per minute is defined as E2. It is preferable that the ratio of the endothermic amounts E2 / E1 is 90% or more. In addition, when carrying out this differential scanning calorimetry, in order to eliminate the influence of the endothermic peak due to enthalpy relaxation, first, 1g of the toner as a sample to be measured is heated to a temperature (60°C in the example described later) exceeding the glass transition temperature Tg of the binder resin (amorphous polyester resin) at a heating rate of 10°C per minute and held for 5 minutes, and then cooled to 30°C at a cooling rate of 10°C per minute and held for 1 minute. Thereafter, the first run is carried out.

[0012] In the two-component developer, it is preferable that the ratio of the area of ​​the portion where the ferrite core material is exposed on the carrier surface is 5% or more and 20% or less.

[0013] In the two-component developer, the particle diameter of the silica particles is preferably 10 nm or more and 100 nm or less.

[0014] In the two-component developer, it is preferable that the adhesion strength of the silica particles to the toner particles is 45% or more and 75% or less, and the adhesion strength of the fatty acid metal salt particles to the toner particles is 25% or less.

[0015] In the two-component developer, the fatty acid of the fatty acid metal salt particles preferably has 12 or more carbon atoms.

[0016] In the two-component developer, the ratio of free fatty acid in the fatty acid metal salt particles is preferably 0.2% or less.

[0017] In the two-component developer, when the particle diameter of the silica particles is Dp and the particle diameter of the fatty acid metal salt particles is Df, it is preferable that Dp / Df is less than 0.15.

[0018] In the above two-component developer, it is preferable that Cp / Cf is less than 10, where Cp is the content of the silica particles in the two-component developer and Cf is the content of the fatty acid metal salt particles.

[0019] Incidentally, Patent Document 1 discloses the use of fatty acid metal salt particles and silica particles surface-treated with silicone oil as external additives for toner, but the toner disclosed in Patent Document 1 is for use with a one-component developer.

[0020] In addition, Patent Document 1 discloses that the amount of silicone oil liberated from silica particles is 50% by mass or less based on the carbon amount, but the "amount of free oil" in the examples of Patent Document 1 is calculated to be at most about 1.5%. This is because Patent Document 1 defines the ratio of the silicone oil liberated from the total amount of silicone oil used in the surface treatment as the "amount of silicone oil liberated", whereas in the present disclosure, as described later, the ratio of the "amount of carbon in the oil-treated silica particles after extraction" to the "amount of carbon in the oil-treated silica particles before extraction" is calculated by using hexane as the extraction solvent, and the ratio of the "amount of carbon lost in the extraction process" to the "amount of carbon in the oil-treated silica particles before extraction" is defined as the "amount of free oil [%]". In other words, in the toner disclosed in Patent Document 1, the amount of free oil is reduced to as little as possible, at most about 1.5%, to obtain the desired characteristics, whereas in the two-component developer of the present disclosure, the amount of free oil is relatively large to obtain the desired characteristics. Effect of the Invention

[0021] The two-component developer of the present disclosure exhibits excellent effects, such as good charge rise throughout the product life, in both low-humidity and high-humidity environments. [Brief description of the drawings]

[0022] [Figure 1] FIG. 2 is a cross-sectional view illustrating a two-component developer according to the present embodiment. [Diagram 2] FIG. 2 is a cross-sectional view illustrating a schematic diagram of the toner according to the present embodiment. [Diagram 3] FIG. 2 is a cross-sectional view illustrating a carrier according to the present embodiment. [Figure 4] 1 is an example of a projection image of a carrier obtained using a scanning electron microscope. [Diagram 5] This is an edited version of the image in Figure 4. [Figure 6] This is an edited version of the image in Figure 5. [Figure 7] This is an edited version of the image in Figure 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Hereinafter, an embodiment of the two-component developer of the present disclosure will be described in detail. First, the characteristics of the two-component developer as a whole will be described, and then the characteristics of the toner and carrier contained in the two-component developer will be described.

[0024] In the present disclosure, "external addition" means adding (adhering) to the surface of a particle, and "internal addition" means adding to the inside of a particle.

[0025] 1. Two-component developer The two-component developer according to the present embodiment is a two-component developer containing a toner and a carrier, as shown in Fig. 1. The two-component developer can be produced by mixing the toner and the carrier using a known mixer. The mass ratio of the toner and the carrier is not particularly limited, and may be, for example, 3:97 to 12:88.

[0026] The two-component developer according to this embodiment is a two-component developer containing a toner having an external additive attached to the surface of the toner particles, and a carrier, wherein the toner particles contain an amorphous polyester resin and a crystalline polyester resin, the external additive contains fatty acid metal salt particles and silica particles surface-treated with silicone oil, the silica particles have a free oil content of 3% or more and 6% or less, the fatty acid metal salt particles have a particle diameter of 0.5 μm or more and 1.5 μm or less, and the carrier has a straight silicone resin coating layer formed on at least a portion of the surface of a ferrite core material.

[0027] As described above, even if silica particles surface-treated with silicone oil are used as an external additive, there is a problem that toner charge-up cannot be suppressed under conditions in which image output continues at low printing (a state in which the ratio of the area of ​​the printed image to the area of ​​the entire recording medium is low) in a low-humidity environment. In response to this problem, in the two-component developer according to this embodiment, by containing a crystalline polyester resin in the toner particles (toner core), the part where the crystalline polyester resin is compatible with the amorphous polyester resin (compatible part 12a shown in FIG. 2) maintains a moderate low resistance and becomes a leak point of charge, so that excessive charge-up in a low-humidity environment can be suppressed. In addition, since PDMS (polydimethylsiloxane, a type of silicone), which is the surface treatment agent in the "silicone oil surface-treated silica particles", has a low SP value, when the oil-treated silica particles adhere to the toner particle surface, they adhere to the part of the toner particle surface where the crystalline polyester resin with a low SP value is exposed (see FIG. 2), so that the effect of suppressing excessive charge-up in a low-humidity environment can be sufficiently obtained. Furthermore, by adjusting the amount of free oil in the oil-treated silica particles to an appropriate level, the charge relaxation points (places that relax charge) on the toner surface can be increased, making it possible to more effectively suppress excessive charge-up in low-humidity environments.

[0028] In addition, as described above, under conditions where the developer is left in a high-humidity environment for a long period of time, the amount of moisture adsorbed to the silica particles surface-treated with silicone oil increases, and the moisture even adheres to the carrier surface, which excessively promotes charge leakage, causing poor charging, and ultimately making fogging more likely to occur. However, this problem can be solved by coating the carrier with a highly hydrophobic material such as silicone resin. However, since the silicone resin coating layer on the carrier surface and the oil-treated silica particles have similar SP values ​​and are compatible with each other, the oil-treated silica particles tend to adhere to the carrier surface (transfer from the toner side to the carrier side). Therefore, there is a problem that it is difficult to maintain the above-mentioned characteristics (the effect of suppressing poor charging and fogging) throughout the product life. In the two-component developer according to this embodiment, by incorporating fatty acid metal salt particles with an appropriate particle size into the external additive of the toner, the fatty acid metal salt particles with the opposite polarity in charging can electrostatically adsorb and collect the oil-treated silica particles attached to the carrier surface, so that the above-mentioned characteristics (the effect of suppressing poor charging and fogging) can be exhibited throughout the product life.

[0029] 2. Toner The toner contained in the two-component developer according to the present embodiment is a toner particle (toner core) having an external additive attached to the surface thereof. The toner particles according to the present embodiment are composed of internal additives such as a colorant, a release agent, and a charge control agent, and a binder resin, and the internal additives are dispersed in the binder resin. Furthermore, as necessary, any optional components may be contained within a range that does not impair the effects of the present disclosure. The average primary particle diameter of the toner particles can be appropriately selected depending on the purpose, and may be, for example, 4 μm or more and 10 μm or less. Below, each material constituting the toner according to the present embodiment will be described.

[0030] <Resin> The toner particles according to the present embodiment contain at least an amorphous polyester resin as a binder resin and a crystalline polyester resin.

[0031] It is generally known that a crystalline polyester resin can lower the softening temperature and melt viscosity of a toner, and can improve the low-temperature fixability of a toner by using it in combination with an amorphous polyester resin. In addition, when the materials of the amorphous polyester resin and the crystalline polyester resin used in combination, specifically, the main components of the dicarboxylic acid monomer and polyhydric alcohol, are different, the compatibility of the two resins can be more reliably suppressed, and a greater effect of improving the low-temperature fixability can be expected. However, by suppressing the compatibility of the two resins, the crystalline polyester resin becomes more likely to be liberated from the amorphous polyester resin, and is more likely to be fixed to the developing roller together with the filler component.

[0032] In the present disclosure, amorphous resins and crystalline resins are distinguished by their crystallinity index, with a resin having a crystallinity index of 0.6 or more and 1.5 or less being crystalline resins, and a resin having a crystallinity index of less than 0.6 or more than 1.5 being amorphous resins. Resins having a crystallinity index of more than 1.5 are amorphous, and resins having a crystallinity index of less than 0.6 have low crystallinity and many amorphous portions.

[0033] The crystallinity index is a physical property that is an index of the degree of crystallization of a resin, and is defined as the ratio of the softening temperature to the highest endothermic peak temperature (softening temperature / highest endothermic peak temperature). Here, the highest endothermic peak temperature refers to the temperature of the highest endothermic peak observed. In a crystalline polyester resin, the highest peak temperature is the melting point Tmp, and in an amorphous polyester resin, the highest endothermic peak is the glass transition temperature Tg.

[0034] The degree of crystallization of the resin can be controlled by adjusting the types and ratio of the monomers used as materials, as well as the production conditions (for example, reaction temperature, reaction time, cooling rate), and the like.

[0035] -Amorphous polyester resin- The amorphous polyester resin contained in the toner particles according to this embodiment is obtained, for example, by a polycondensation reaction between a carboxylic acid monomer containing terephthalic acid or isophthalic acid as a main component and a polyhydric alcohol containing ethylene glycol as a main component.

[0036] The reaction conditions are the same as those for producing ordinary polyester resins, and for example, a dicarboxylic acid monomer and a polyhydric alcohol are reacted in a nitrogen gas atmosphere, optionally in the presence of an esterification catalyst, at 190° C. to 240° C. to obtain an amorphous polyester resin. The reaction ratio of the polyhydric alcohol to the carboxylic acid monomer is preferably 1.3:1 to 1:1.2 in terms of the equivalent ratio of hydroxyl groups to carboxy groups [OH]:[COOH].

[0037] The dicarboxylic acid monomer used in the synthesis of the amorphous polyester resin contains terephthalic acid or isophthalic acid as a main component, and the molar content of terephthalic acid or isophthalic acid in the dicarboxylic acid monomer is preferably 70% or more and 100% or less, and more preferably 80% or more and 100% or less.

[0038] The dicarboxylic acid monomer may contain an aromatic dicarboxylic acid or an aliphatic dicarboxylic acid other than terephthalic acid and isophthalic acid. Examples of aromatic dicarboxylic acids other than terephthalic acid and isophthalic acid include fumaric acid, and examples of aliphatic dicarboxylic acids include adipic acid, sebacic acid, and succinic acid. The dicarboxylic acid monomer may contain an ester-forming derivative of terephthalic acid or isophthalic acid, an ester-forming derivative of an aromatic dicarboxylic acid other than terephthalic acid and isophthalic acid, or an ester-forming derivative of an aliphatic dicarboxylic acid. In the present disclosure, the ester-forming derivative includes an acid anhydride, an alkyl ester, or the like of a carboxylic acid. Note that these dicarboxylic acid monomers may be used alone or in combination of two or more.

[0039] In the synthesis of the amorphous polyester resin, a polycarboxylic acid monomer having three or more valences may be used together with the dicarboxylic acid monomer. As the polycarboxylic acid monomer having three or more valences, a polycarboxylic acid having three or more valences, such as trimellitic acid and pyromellitic acid, and an ester-forming derivative thereof may be used. These polycarboxylic acid monomers having three or more valences may be used alone or in combination of two or more kinds.

[0040] The diol monomer used in the synthesis of the amorphous polyester resin contains ethylene glycol as a main component, and the molar content of ethylene glycol in the diol monomer is preferably 70% or more and 100% or less, and more preferably 80% or more and 100% or less.

[0041] The diol monomer may include 1,3-propylene glycol, 1,4-butanediol, etc. These diol monomers may be used alone or in combination of two or more.

[0042] From the viewpoint of the fixing property, storage stability, durability, etc. of the toner, the amorphous polyester resin preferably has a glass transition temperature Tg of 50° C. or more and 70° C. or less. If the glass transition temperature is outside this range, the balance between the fixing property, storage stability, and durability of the toner may be lost.

[0043] In addition, from the viewpoint of achieving both low-temperature fixing properties and hot offset resistance of the toner, it is preferable that the amorphous polyester resin has a softening temperature Tm of 100° C. or more and 150° C. or less. If the softening temperature is outside this range, the balance between the low-temperature fixing properties and hot offset resistance of the toner may be lost.

[0044] From the viewpoint of achieving both the heat-resistant storage stability and low-temperature fixability of the toner, the amorphous polyester resin preferably has a peak top molecular weight Mp of 3,000 or more and 10,500 or less. If the peak top molecular weight is outside this range, the balance between the heat-resistant storage stability and low-temperature fixability of the toner may be lost.

[0045] Here, the peak top molecular weight Mp means the molecular weight showing the maximum peak height of the THF soluble matter in gel permeation chromatography (GPC) using tetrahydrofuran (THF) as the mobile phase and polystyrene as the standard substance.

[0046] In addition, the amorphous polyester resin preferably has an acid value of 0 mgKOH or more and 60 mgKOH / g or less from the viewpoint of the chargeability of the toner, and a hydroxyl value of 0 mgKOH / g or more and 50 mgKOH / g or less from the viewpoint of the hot offset resistance of the toner. If the acid value exceeds 60 mgKOH / g, the chargeability of the toner may deteriorate, and if the hydroxyl value exceeds 50 mgKOH / g, the hot offset resistance of the toner may become insufficient.

[0047] The amorphous polyester resin preferably has an SP value (solubility parameter) of 10.5 or more and 12.5 or less. If the SP value is less than 10.5, the compatibility with the crystalline polyester resin may progress too much, and the blocking resistance and hot offset resistance of the toner may be impaired. On the other hand, if the SP value exceeds 12.5, the compatibility with the crystalline polyester resin may be too low, and the low-temperature fixability may be insufficient.

[0048] -Crystalline polyester resin- As shown in Fig. 2, in the toner particles according to the present embodiment, the crystalline polyester resin is dispersed in the amorphous polyester resin. The crystalline polyester resin is preferably composed of a linear saturated aliphatic polyester unit obtained by polycondensation of a carboxylic acid monomer containing, as a main component, an aliphatic dicarboxylic acid having 9 to 22 carbon atoms, and a polyhydric alcohol containing, as a main component, an aliphatic diol having 2 to 10 carbon atoms.

[0049] The reaction conditions are the same as those for producing a normal polyester resin, and for example, a crystalline polyester resin is obtained by reacting a carboxylic acid monomer with a polyhydric alcohol in a nitrogen gas atmosphere, optionally in the presence of an esterification catalyst, at 190° C. to 240° C. From the viewpoint of the storage stability of the toner, the reaction ratio of the polyhydric alcohol to the carboxylic acid monomer is preferably 0.83:1 to 1.3:1 in terms of the equivalent ratio of hydroxyl groups to carboxy groups [OH]:[COOH].

[0050] It is preferable that the molar content of dicarboxylic acid in the carboxylic acid monomer is 90% or more and 100% or less. If the molar content of dicarboxylic acid is low, the rate and speed of crystallization may decrease, and the toner aggregation resistance (resistance to toner aggregation) may become insufficient.

[0051] Examples of the aliphatic dicarboxylic acid having 9 to 22 carbon atoms include azelaic acid, sebacic acid, 1,10-decanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid. The dicarboxylic acid monomer may also contain an ester-forming derivative of these aliphatic dicarboxylic acids. These dicarboxylic acid monomers may be used alone or in combination of two or more.

[0052] In the synthesis of the crystalline polyester resin, a polycarboxylic acid monomer having three or more valences may be used together with the dicarboxylic acid monomer. As the polycarboxylic acid monomer having three or more valences, a polycarboxylic acid having three or more valences, such as trimellitic acid and pyromellitic acid, and an ester-forming derivative thereof may be used. These polycarboxylic acid monomers having three or more valences may be used alone or in combination of two or more kinds.

[0053] The molar content of the aliphatic diol having 2 to 10 carbon atoms in the polyhydric alcohol is preferably 80% or more and 100% or less.

[0054] Examples of the aliphatic diol having 2 to 10 carbon atoms include ethylene glycol, 1,4-butanediol, 1,6-hexanediol, etc. These diol monomers may be used alone or in combination of two or more.

[0055] In the synthesis of the crystalline polyester resin, a polyol monomer having three or more valences may be used together with the diol monomer. As the polyol monomer having three or more valences, glycerin, trimethylolpropane, etc. can be used. These polyol monomers having three or more valences may be used alone or in combination of two or more.

[0056] In the differential scanning calorimetry of the toner according to the present embodiment, the amount of heat absorbed by the crystalline polyester resin in the 1st run, in which the toner is heated from 30°C to 150°C at a heating rate of 10°C per minute, is defined as E1, and the amount of heat absorbed by the crystalline polyester resin in the 2nd run, in which the toner is cooled to 30°C at a cooling temperature of 10°C per minute after the 1st run and held for 1 minute, is heated again from 30°C to 150°C at a heating rate of 10°C per minute, is defined as E2. The ratio of the amount of heat absorbed, E2 / E1, is preferably 90% or more, more preferably 95% or more. When the ratio of the amount of heat absorbed, E2 / E1, is within the above range, the crystalline polyester resin is finely dispersed in the amorphous polyester resin and is in a state of being appropriately compatible (a state in which the compatible portion 12a shown in FIG. 2 is appropriately present). This maintains the durability of the toner, thereby maintaining performance throughout the product life, and a two-component developer with good charge rise in both low humidity and high humidity environments can be realized. In carrying out this differential scanning calorimetry, first, in order to eliminate the influence of endothermic peaks due to enthalpy relaxation, 1 g of toner as a sample to be measured is heated at a heating rate of 10°C per minute to a temperature exceeding the glass transition temperature Tg of the binder resin (amorphous polyester resin) (60°C in the examples described later) and held for 5 minutes, and then cooled at a cooling rate of 10°C per minute to 30°C and held for 1 minute. Then, the 1st run is carried out.

[0057] The melting point Tmp of the crystalline polyester resin is preferably from 40° C. to 90° C., more preferably from 60° C. to 90° C., from the viewpoint of the fixing property, storage stability, durability, etc. of the toner. If the melting point is less than 40° C., the durability of the toner may be insufficient. If the melting point is more than 90° C., the fixing property of the toner may be insufficient.

[0058] From the viewpoint of low-temperature fixing property and blocking resistance of the toner, the softening temperature Tm of the crystalline polyester resin is preferably 65° C. or more and 110° C. or less. If the softening temperature is outside this range, the low-temperature fixing property and blocking resistance of the toner may become insufficient.

[0059] Furthermore, from the viewpoint of crystallization speed and blocking resistance, the crystalline polyester resin preferably has a ratio of the softening temperature Tm to the melting point Tmp, "Tm / Tmp", of 1.0 to 1.4. If Tm / Tmp is out of this range, the crystallization speed and blocking resistance may be insufficient.

[0060] From the viewpoint of the storage stability and low-temperature fixing property of the toner, the crystalline polyester resin preferably has a peak top molecular weight Mp of 10,000 or more and 90,000 or less. If the peak top molecular weight is outside this range, the storage stability and low-temperature fixing property of the toner may become insufficient.

[0061] From the viewpoint of the chargeability of the toner, the crystalline polyester resin preferably has an acid value of 0 mgKOH or more and 60 mgKOH / g or less, and from the viewpoint of the hot offset resistance of the toner, preferably has a hydroxyl value of 0 mgKOH / g or more and 40 mgKOH / g or less. If the acid value exceeds 60 mgKOH / g, the chargeability of the toner may deteriorate, and if the hydroxyl value exceeds 40 mgKOH / g, the hot offset resistance of the toner may become insufficient.

[0062] The SP value of the crystalline polyester resin is preferably 9.0 or more and 9.8 or less, depending on the relationship with the SP value of the amorphous polyester resin. If the SP value of the crystalline polyester resin is less than 9.0, the compatibility with the amorphous polyester resin may be too low, and the durability of the toner may be insufficient. If the SP value of the crystalline polyester resin is more than 9.8, the glass transition temperature of the resin constituting the toner particles may be lowered, and the blocking resistance of the toner may be reduced.

[0063] <Internal additives> -wax- The toner particles according to the present embodiment may contain a wax as a release agent. As the wax, waxes used in the field of electrophotography may be used, for example, paraffin wax, microcrystalline wax, Fischer-Tropsch wax, polyethylene wax, polypropylene wax, carnauba wax, synthetic ester wax, etc. These waxes may be used alone or in combination of two or more. The content of the wax in the toner particles is not particularly limited, but is preferably 0.5% by mass to 10% by mass.

[0064] -Coloring agent- The toner particles according to the present embodiment may contain a colorant. As the colorant, organic pigments, organic dyes, inorganic pigments, inorganic dyes, and the like used in the field of electrophotography can be used.

[0065] Examples of black colorants include carbon black, copper oxide, manganese dioxide, aniline black, activated carbon, non-magnetic ferrite, magnetic ferrite, and magnetite.

[0066] Examples of yellow colorants include CI Pigment Yellow 12, CI Pigment Yellow 13, CI Pigment Yellow 14, CI Pigment Yellow 15, CI Pigment Yellow 17, CI Pigment Yellow 74, CI Pigment Yellow 93, CI Pigment Yellow 94, CI Pigment Yellow 138, CI Pigment Yellow 180, and CI Pigment Yellow 185.

[0067] Examples of magenta colorants include CI Pigment Red 48:1, CI Pigment Red 53:1, CI Pigment Red 57:1, CI Pigment Red 122, CI Pigment Red 123, CI Pigment Red 139, CI Pigment Red 144, CI Pigment Red 149, CI Pigment Red 166, CI Pigment Red 177, CI Pigment Red 178, and CI Pigment Red 222.

[0068] Examples of cyan colorants include CI Pigment Blue 15, CI Pigment Blue 15:2, CI Pigment Blue 15:3, CI Pigment Blue 16, CI Pigment Blue 60, and the like.

[0069] The content of the colorant is not particularly limited, but is preferably 5 parts by mass or more and 15 parts by mass or less with respect to 100 parts by mass of the binder resin. Note that the colorant may be used in the form of a master batch in order to disperse it uniformly in the binder resin.

[0070] -Charge adjustment agent- The toner particles according to the present embodiment may contain a charge control agent. The charge control agent is added to impart a preferable charge property to the toner. The charge control agent is not particularly limited, and charge control agents for positive charge control and negative charge control used in the electrophotographic field can be used.

[0071] Examples of charge control agents for controlling positive charges include quaternary ammonium salts, pyrimidine compounds, triphenylmethane derivatives, guanidine salts, and amidine salts.

[0072] Charge control agents for negative charge control include metal-containing azo compounds, azo complex dyes, metal complexes and metal salts of salicylic acid and its derivatives (metals include chromium, zinc, zirconium, etc.), organic bentonite compounds, and boron compounds.

[0073] <External additives> The toner in the two-component developer according to the present embodiment contains, as an external additive, fatty acid metal salt particles and silica particles surface-treated with silicone oil. In this disclosure, the silica particles before surface-treatment with silicone oil are referred to as a "silica base material."

[0074] Regarding the adhesion strength of the external additive to the toner particles according to the present embodiment, the adhesion strength of the oil-treated silica particles is preferably 45% or more and 75% or less, more preferably 50% or more and 60% or less. Also, the adhesion strength of the fatty acid metal salt particles is preferably 25% or less, more preferably 20% or less. By having the adhesion strength of the oil-treated silica particles within the above range, the above-mentioned charge-up suppression effect can be more effectively exhibited, and by having the adhesion strength of the fatty acid metal salt particles within the above range, the above-mentioned effect of electrostatically adsorbing and recovering the oil-treated silica particles attached to the carrier surface can be more effectively exhibited.

[0075] In the two-component developer according to the present embodiment, the particle diameter of the oil-treated silica particles is Dp, and the particle diameter of the fatty acid metal salt particles is Df, and Dp / Df is preferably 0.01 or more and less than 0.15, and more preferably 0.02 or more and less than 0.10. By having the particle diameter ratio Dp / Df within the above range, the ability of the fatty acid metal salt particles to electrostatically adsorb and collect the oil-treated silica particles attached to the carrier surface can be further improved.

[0076] In the two-component developer according to this embodiment, if the content of the oil-treated silica particles is Cp and the content of the fatty acid metal salt particles is Cf, then Cp / Cf is preferably 1 or more and less than 10, and more preferably 3 or more and less than 7. When the content ratio Cp / Cf is within the above range, the ability of the fatty acid metal salt particles to electrostatically adsorb and collect the oil-treated silica particles adhering to the carrier surface can be further improved.

[0077] -Silica particles surface-treated with silicone oil- Silica particles surface-treated with silicone oil (oil-treated silica particles) are particles formed from a silica base material (silica particles before surface treatment) and silicone oil. The specific surface area of ​​the particles as measured by the BET method is, but is not limited to, 30 m 2 ~400m 2 / g.

[0078] The silica substrate can be manufactured by known methods such as dry method (gas phase method), wet method, sol-gel method, etc., and the one manufactured by gas phase method is preferable because it does not use solvent.The gas phase method is a method for producing a silica substrate by the vapor phase oxidation of a silicon halogen compound, and for example, the silica substrate called dry method (gas phase method) silica or fumed silica can be manufactured by the thermal decomposition oxidation reaction (basic reaction: SiCl4+2H2+O2→SiO2+4HCl) of silicon tetrachloride gas in an oxyhydrogen flame.

[0079] The silica substrate may also be a composite of silica and another metal oxide, which is obtained by using a metal halide compound such as aluminum chloride or titanium chloride together with a silicon halide compound in the above-mentioned production process.

[0080] Silica particles surface-treated with silicone oil can be produced, for example, by a method in which a silica base material treated with an organosilicon compound and silicone oil are directly mixed using a mixer such as a Henschel mixer; a method in which silicone oil diluted with an appropriate solvent such as normal hexane is sprayed onto a silica base material and then heat-treated; or a method in which silicone oil is dissolved or dispersed in an appropriate solvent, the silica base material is added and mixed, and the solvent is then removed.

[0081] The heat treatment after the spraying is preferably carried out in an inert gas atmosphere such as helium, nitrogen, argon, etc., for safety reasons, and is preferably carried out in a nitrogen gas atmosphere in consideration of costs, etc. The temperature of this heat treatment is preferably 200°C or higher and 400°C or lower.

[0082] Examples of the silicone oil include straight silicone oils such as dimethyl silicone oil, methylphenyl silicone oil, and methylhydrogen silicone oil; epoxy-modified silicone oil, carboxyl-modified silicone oil, carbinol-modified silicone oil, methacrylic-modified silicone oil, mercapto-modified silicone oil, phenol-modified silicone oil, one-end reactive modified silicone oil, heterogeneous functional group modified silicone oil, polyether-modified silicone oil, methylstyryl-modified silicone oil, alkyl-modified silicone oil, higher fatty acid ester-modified silicone oil, hydrophilic special modified silicone oil, higher alkoxy-modified silicone oil, higher fatty acid-containing modified silicone oil, and fluorine-modified silicone oil. These may be used alone or in combination of two or more.

[0083] Examples of the organosilicon compound include hexamethyldisilazane, trimethylsilane, trimethylethoxysilane, isobutyltrimethoxysilane, trimethylchlorosilane, dimethyldichlorosilane, methyltrichlorosilane, dimethylethoxysilane, dimethyldimethoxysilane, diphenyldiethoxysilane, hexamethyldisiloxane, etc. These may be used alone or in combination of two or more.

[0084] Silica particles surface-treated with silicone oil can be produced, for example, by the method described in Japanese Patent No. 6849352. The desired particles can be obtained by changing the average primary particle size of the silica base material and the amount of silicone oil used.

[0085] In the two-component developer according to the present embodiment, the content of the silica particles surface-treated with silicone oil is preferably 0.2 parts by mass or more and 2.0 parts by mass or less, more preferably 0.4 parts by mass or more and 1.8 parts by mass or less, and even more preferably 0.5 parts by mass or more and 1.5 parts by mass or less, relative to 100 parts by mass of toner particles. If the content of the oil-treated silica particles is less than the lower limit, the effect of adding the oil-treated silica particles described above may not be fully obtained. If the content of the oil-treated silica particles exceeds the upper limit, as the use time of the two-component developer increases (as the product life progresses), the oil-treated silica particles migrate from the toner particle surface to the carrier surface, which reduces the charging ability of the carrier, making fogging more likely to occur in the latter half of the product life, and ultimately causing image defects.

[0086] In the two-component developer according to the present embodiment, the free oil amount of the silica particles surface-treated with silicone oil is 3% or more and 6% or less, and more preferably 4% or more and 5% or less. By keeping the free oil amount within the above range, the points that alleviate the charge on the toner surface can be increased, and the effect of suppressing excessive charge-up in a low-humidity environment can be improved. The method for measuring the free oil amount will be described in the Examples section below.

[0087] In the two-component developer according to the present embodiment, the particle diameter of the oil-treated silica particles is preferably 10 nm to 100 nm, more preferably 20 nm to 60 nm, and even more preferably 30 nm to 50 nm. By having the particle diameter within the above range, the adhesion strength of the oil-treated silica particles to the toner tends to be appropriate, and the charge rise can be improved throughout the product life in both low-humidity and high-humidity environments.

[0088] -Fatty acid metal salt particles- The fatty acid metal salt particles are salt particles composed of a fatty acid and a metal. The fatty acid may be a saturated fatty acid or an unsaturated fatty acid. The carbon number of the fatty acid in the fatty acid metal salt particles is 10 to 25, preferably 12 to 22, and more preferably 16 or more. The carbon number of the fatty acid includes the carbon of the carboxy group. By making the carbon number of the fatty acid 16 or more (the carbon number of the long chain hydrocarbon part of the fatty acid is 15 or more), the hydrophobicity is increased, and the above-mentioned effect of electrostatically adsorbing and recovering the oil-treated silica particles attached to the carrier surface can be more effectively exhibited.

[0089] Examples of fatty acids include unsaturated fatty acids such as behenic acid, stearic acid, palmitic acid, myristic acid, lauric acid, etc., and unsaturated fatty acids such as oleic acid, linoleic acid, ricinoleic acid, etc. Among these fatty acids, fatty acids having 16 or more carbon atoms are preferred, and among these, stearic acid is more preferred.

[0090] The metal is preferably a divalent metal, such as magnesium, calcium, aluminum, barium, or zinc, with zinc being particularly preferred.

[0091] Examples of fatty acid metal salt particles include metal salts of stearic acid such as aluminum stearate, calcium stearate, potassium stearate, magnesium stearate, barium stearate, lithium stearate, zinc stearate, copper stearate, lead stearate, nickel stearate, strontium stearate, cobalt stearate, and sodium stearate; palmitate particles such as zinc palmitate, cobalt palmitate, copper palmitate, magnesium palmitate, aluminum palmitate, and calcium palmitate; Examples of the metal salts include particles of metal salts of mitic acid, metal salts of lauric acid such as zinc laurate, manganese laurate, calcium laurate, iron laurate, magnesium laurate, and aluminum laurate, metal salts of oleic acid such as zinc oleate, manganese oleate, iron oleate, aluminum oleate, copper oleate, magnesium oleate, and calcium oleate, metal salts of linoleic acid such as zinc linoleate, cobalt linoleate, and calcium linoleate, and metal salts of ricinoleic acid such as zinc ricinoleate and aluminum ricinoleate, etc. Among these, particles of metal salts of stearic acid are preferred.

[0092] The method for producing fatty acid metal salt particles is not particularly limited, and examples thereof include a method of cationic substitution of fatty acid alkali metal salt, a method of directly reacting fatty acid with metal hydroxide, etc. As an example of a method for producing zinc stearate particles as fatty acid metal salt particles, examples thereof include a method of cationic substitution of sodium stearate, a method of reacting stearic acid with zinc hydroxide, etc.

[0093] The content of the fatty acid metal salt particles in the two-component developer according to this embodiment is preferably 0.05 parts by mass to 1 part by mass, more preferably 0.10 parts by mass to 0.50 parts by mass, per 100 parts by mass of the toner particles.

[0094] In the two-component developer according to the present embodiment, the fatty acid metal salt particles have a particle size of 0.5 μm to 1.5 μm, preferably 0.7 μm to 1.0 μm. By having the particle size within the above range, the fatty acid metal salt particles tend to have an appropriate adhesion strength to the toner, and the oil-treated silica particles adhering to the carrier surface can be electrostatically adsorbed and collected, thereby more effectively exerting the above-mentioned effect.

[0095] In the two-component developer according to the present embodiment, the ratio of free fatty acid in the fatty acid metal salt particles is preferably 0.2% or less, more preferably 0.15% or less. By having the ratio of free fatty acid within the above range, the above-mentioned effect of electrostatically adsorbing and recovering the oil-treated silica particles attached to the carrier surface can be exhibited throughout the product life. If the amount of free fatty acid in the fatty acid metal salt particles is large, as the usage time of the two-component developer increases (as the product life progresses), the free fatty acid is adsorbed to the carrier surface, and the free oil of the oil-treated silica particles is also adsorbed to the carrier surface, which may cause excessive charge leakage and may prevent the effect of maintaining good charge rise from being exhibited. The lower limit of the ratio of free fatty acid in the fatty acid metal salt particles is 0.01% or more.

[0096] 3. Career As shown in Fig. 3, the carrier contained in the two-component developer according to this embodiment is a resin-coated carrier. The resin-coated carrier is composed of a carrier core material and a resin coating layer that coats the surface of the carrier core material. In the carrier according to this embodiment, a straight silicone resin coating layer is formed on at least a part of the surface of the ferrite core material as the carrier core material.

[0097] In the two-component developer according to the present embodiment, the ratio of the area of ​​the part where the ferrite core material is exposed on the carrier surface (hereinafter, also referred to as the core material exposed area ratio) is preferably 5% to 20%, more preferably 10% to 20%. By setting the core material exposed area ratio within the above range, it is possible to further enhance the effect of suppressing charge-up in a low humidity environment and the effect of suppressing charge leakage in a high humidity environment.

[0098] <Carrier core material> The ferrite core material as the carrier core material is composed of ferrite, which is a magnetic metal oxide. In the two-component developer according to the present embodiment, the ferrite core material is suitable from the viewpoint of realizing a resin-coated carrier having excellent chargeability and durability and saturation magnetization suitable for a full-color image forming device.

[0099] The ferrite core material preferably has a volume average particle diameter of 35 μm or more and 55 μm or less. By setting the volume average particle diameter of the ferrite core material within the above range, toner transportation is stabilized and high-definition image formation is possible. If the volume average particle diameter of the ferrite core material is less than 35 μm, the resin-coated carrier tends to have a small volume average particle diameter, which may increase carrier adhesion. If the volume average particle diameter of the ferrite core material is more than 55 μm, the resin-coated carrier tends to have a large volume average particle diameter, which may deteriorate the graininess of the image.

[0100] <Resin coating layer> The straight silicone resin coating layer of the carrier according to this embodiment can be formed by coating the surface of the carrier core with a resin coating layer composition. The resin coating layer composition can be produced by mixing a predetermined amount of crosslinked silicone resin with an additive that is added in an appropriate amount as necessary. Examples of additives include conductive particles, amino group-containing silane coupling agents, bifunctional silicone oils, etc., and these may be used alone or in combination of two or more.

[0101] <Straight silicone resin> A straight silicone resin is used as the resin for forming the resin coating layer. By using a straight silicone resin, the releasability of the toner from the carrier during development can be improved, and good developability can be realized. In addition, the resin coating layer can be made to have a desired hardness, and the adhesion to the carrier core material is also good. Furthermore, the hydrophobicity of the carrier surface can be increased, so that stable charging properties in a high humidity environment and toner spent resistance (resistance to toner spent) throughout the product life can be improved. In turn, a two-component developer that can stably charge the toner for a long period of time can be realized.

[0102] In the carrier according to the present embodiment, the content of the straight silicone resin is preferably 0.4 parts by mass or more and 2.5 parts by mass or less with respect to 100 parts by mass of the carrier core material. If the content of the straight silicone resin is less than the lower limit, the ratio of the area of ​​the carrier core material exposed on the carrier surface increases, which may make the carrier more susceptible to environmental changes, particularly humidity. If the content of the straight silicone resin exceeds the upper limit, the straight silicone resin cannot be applied uniformly to the carrier core material surface, and the carrier particles may aggregate, which may cause the carrier yield to deteriorate.

[0103] The silicone resin forming the resin coating layer may be a combination of two or more silicone resins having different weight average molecular weights. When the weight average molecular weight of the silicone resin having the smallest weight average molecular weight among the two or more silicone resins contained in the resin coating layer is Ma, and the weight average molecular weight of the silicone resin having the largest weight average molecular weight is Mb, it is preferable to select a silicone resin such that Ma and Mb satisfy the following formula (1). log(Mb / Ma)>2 (1)

[0104] By using two or more silicone resins that satisfy the above formula (1), the resin coating layer can be made to have the desired hardness, and the surface of the carrier core material can be uniformly coated. In addition, the adhesion to the carrier core material is improved, so that the effect of stably charging the toner over a long period of time can be further improved. Ma is 3.0×10 2 Above 5.0×10 3 It is preferable that Mb is 5.0×10 or less. 4 Above 5.0×10 5 It is preferable that:

[0105] The content of the silicone resin having a weight average molecular weight Ma is preferably 0.2 to 1.0 parts by mass per 100 parts by mass of the carrier core material, and the content of the silicone resin having a weight average molecular weight Mb is preferably 0.2 to 1.0 parts by mass per 100 parts by mass of the carrier core material. The ratio of the content of the silicone resin having a weight average molecular weight Ma to the content of the silicone resin having a weight average molecular weight Mb is preferably 1:4 to 4:1.

[0106] When three or more types of silicone resins are used, the weight-average molecular weight of the silicone resins having a weight-average molecular weight greater than Ma and smaller than Mb is not particularly limited, and the content of the silicone resins is also not particularly limited as long as the content of the silicone resins as a whole is not too high.

[0107] As the resin used to form the resin coating layer, among the straight silicone resins, a crosslinked straight silicone resin is more preferable. When the resin coating layer contains a crosslinked straight silicone resin, the releasability of the toner from the carrier during development can be further improved. In addition, the hydrophobicity of the carrier surface is increased, so that the developability throughout the product life can be further improved. Therefore, it is preferable that all the resins contained in the resin coating layer are crosslinked straight silicone resins.

[0108] A crosslinked silicone resin is a silicone resin that is cured by crosslinking between hydroxyl groups bonded to Si atoms or between a hydroxyl group and an -OX group via a thermal dehydration reaction, a room temperature curing reaction, or the like, as shown in the chemical formula below. In the formula below, R represents a monovalent organic group, and multiple Rs may be the same or different. The -OX group is an acetoxy group, an aminoxy group, an alkoxy group, an oxime group, or the like.

[0109] [ka]

[0110] The crosslinked silicone resin is not particularly limited, and either a heat-curable silicone resin or a room-temperature-curable silicone resin can be used. To crosslink a heat-curable silicone resin, the resin needs to be heated to about 200°C to 250°C. To cure a room-temperature-curable silicone resin, heating is not required, but it is preferable to heat the resin at 150°C to 280°C in order to shorten the curing time.

[0111] Among crosslinked silicone resins, those in which the monovalent organic group represented by R is a methyl group are preferred. Crosslinked silicone resins in which R is a methyl group have a dense crosslinked structure, so when a resin coating layer of a carrier core material is formed using a crosslinked silicone resin, a carrier with good water repellency, moisture resistance, etc. is obtained. However, if the crosslinked structure becomes too dense, the resin coating layer tends to become brittle, so it is important to select a silicone resin having a weight average molecular weight that satisfies the above formula (1).

[0112] The mass ratio Si / C of silicon to carbon in the crosslinked silicone resin is preferably 0.3 or more and 2.2 or less. If Si / C is less than the lower limit, the hardness of the resin coating layer may decrease, and the life of the carrier may be shortened. If Si / C exceeds the upper limit, the ability of the carrier to impart charge to the toner may be easily affected by temperature changes, and the resin coating layer may become brittle.

[0113] Examples of commercially available crosslinked silicone resins include SR2400, SR2410, SR2411, SR2510, SR2405, 840RESIN, 804RESIN (all trade names, manufactured by Dow Corning Toray Co., Ltd.), KR271, KR272, KR274, KR216, KR280, KR282, KR261, KR260, KR255, KR266, KR251, KR155, KR152, KR214, KR220, X-4040-171, KR201, KR5202, KR3093, KR240, KR350, KR400 (all trade names, manufactured by Shin-Etsu Chemical Co., Ltd.), and TSR127B (trade name, manufactured by Momentive Performance Materials Japan, LLC). It is preferable to select at least two types of silicone resins from these so that the weight average molecular weight satisfies the above formula (1).

[0114] <Conductive particles> The resin coating layer preferably contains conductive particles, which enhances the carrier's ability to impart charge to the toner, enabling the toner to be charged more stably over a long period of time.

[0115] As the conductive particles, for example, oxides such as conductive carbon black, conductive titanium oxide, and tin oxide can be used. Carbon black is suitable for achieving conductivity with a small amount of addition, but when applied to color toners, carbon may be detached from the resin coating layer. In such cases, it is preferable to use conductive titanium oxide doped with antimony. These conductive particles may be used alone or in combination of two or more types.

[0116] The volume average particle size of the conductive particles is not particularly limited, but is preferably 0.02 μm or more and 2 μm or less, and more preferably 0.02 μm or more and 1 μm or less. The volume average particle size is a value measured using a laser diffraction / scattering type particle size measuring device (for example, Model "LA-920" manufactured by Horiba, Ltd.).

[0117] The content of the conductive particles in the resin coating layer is preferably 30 parts by mass or less, more preferably 1 part by mass or more and 30 parts by mass or less, relative to 100 parts by mass of the silicone resin. By having the content of the conductive particles within the above range, the conductive particles are less likely to fall off from the resin coating layer, and adverse effects on color images can be suppressed. In addition, the mechanical strength of the resin coating layer and the adhesion to the carrier core material can be increased, so that the toner can be charged stably for a long period of time. In addition, a two-component developer that can form high-quality images more stably for a long period of time can be realized.

[0118] If the content of the conductive particles exceeds the upper limit, the conductive particles may easily fall off from the resin coating layer, which may adversely affect the color image. In addition, the mechanical strength of the resin coating layer and the adhesion to the carrier core material may become insufficient, and the resin coating layer may peel off and the carrier core material may be exposed. If the resin coating layer peels off and the carrier core material is exposed, the chargeability may change from the initial carrier, and the toner may not be stably charged. If the content of the conductive particles is less than the lower limit, the effect of adding the conductive particles may not be exhibited, and the toner may not be given a sufficient charge.

[0119] <Coupling Agent> The resin coating layer may further contain a coupling agent such as a silane coupling agent for the purpose of adjusting the toner charge amount. Among the silane coupling agents, a silane coupling agent having an electron-donating functional group is preferred, and an amino group-containing silane coupling agent is more preferred. As an amino group-containing silane coupling agent, for example, one represented by the following formula (2) can be mentioned. (Y) n Si(R) m (Z) q (2) (In the formula, m R's and q Z's are the same or different alkyl groups, alkoxy groups, or chlorine atoms. n Y's are the same or different amino group-containing hydrocarbon groups. m and n each are an integer of 1 to 3, and m+q+n=4.)

[0120] In the above formula (2), examples of the alkyl group represented by R and Z include linear or branched alkyl groups having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, and a tert-butyl group. Of these, a methyl group and an ethyl group are preferred.

[0121] In the above formula (2), examples of the alkoxy group represented by R and Z include linear or branched alkoxy groups having 1 to 4 carbon atoms, such as a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, a butoxy group, an isobutoxy group, and a tert-butoxy group. Of these, a methoxy group and an ethoxy group are preferred.

[0122] In the above formula (2), examples of the hydrocarbon group containing an amino group represented by Y include -(CH2) a Examples of the alkyl group include -X (wherein X is an amino group, an aminocarbonylamino group, an aminoalkylamino group, a phenylamino group or a dialkylamino group, and a is an integer of 1 to 4), -Ph-X (wherein X is the same as above, and -Ph- is a phenylene group), and the like.

[0123] Specific examples of the amino group-containing silane coupling agent include the following: H2N(H2C)3Si(OCH3)3 H2N(H2C)3Si(OC2H5)3 H2N(H3C)3Si(CH3)(OCH3)2 H2N(H2C)2HN(H2C)3Si(CH3)(OCH3)2 H2NOCHN(H2C)3Si(OC2H5)3 H2N(H2C)2HN(H2C)3Si(OCH3)3 H2N-Ph-Si(OCH3)3 (wherein -Ph- represents a p-phenylene group) Ph-HN(H2C)3Si(OCH3)3 (wherein Ph- represents a phenyl group) (H9C4)3N(H2C)3Si(OCH3)3

[0124] The above coupling agent may be used alone or in combination of two or more. The content of the coupling agent can be appropriately selected from within a range that can provide a sufficient charge to the toner and does not significantly reduce the mechanical strength of the resin coating layer, but is preferably 10 parts by mass or less, more preferably 0.01 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the resin coating layer composition.

[0125] <Method of forming resin coating layer> The resin coating layer composition may be in the form of a solution (dispersion) in which the material of the resin coating layer composition is dissolved or dispersed in an organic solvent. The organic solvent is not particularly limited as long as it can dissolve the silicone resin, and examples thereof include aromatic hydrocarbons such as toluene and xylene; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran and dioxane; and higher alcohols. These may be used alone or in combination of two or more to form a mixed solvent. By using this resin coating layer composition in the form of a solution (hereinafter also referred to as "coat resin liquid"), a resin coating layer can be formed on the surface of the carrier core material.

[0126] A method for forming a resin coating layer using a coating resin liquid includes, for example, applying the coating resin liquid to the surface of a carrier core material to form a coating layer, volatilizing and removing the organic solvent from the coating layer by heating (drying the coating layer), and heat-curing or simply curing the coating layer during or after the drying to form a resin coating layer.

[0127] Examples of methods for applying the coating resin liquid to the surface of the carrier core material include a dipping method in which the carrier core material is impregnated with the coating resin liquid, a spray method in which the coating resin liquid is sprayed onto the carrier core material, a fluidized bed method in which the coating resin liquid is sprayed onto the carrier core material in a floating state by a flowing air current, etc. Among these, the dipping method is preferred because it can easily form a resin coating layer and easily control the ratio of the exposed area of ​​the core material.

[0128] For the drying of the coating layer, a drying accelerator may be used. Known drying accelerators can be used, such as metal soaps which are salts of fatty acids such as naphthenic acid and octylic acid and metals such as lead, iron, cobalt, manganese, and zinc; organic amines such as ethanolamine, etc.

[0129] The curing of the coating layer is preferably carried out while selecting the heating temperature according to the type of crosslinked silicone resin. For example, it is preferably carried out by heating to about 150°C to 280°C. When the crosslinked silicone resin is of the type that cures at room temperature, heating is not essential, but for the purpose of enhancing the mechanical strength of the formed resin coating layer, shortening the curing time, etc., it may be heated to about 150°C to 280°C.

Examples

[0130] Hereinafter, based on examples and comparative examples, the two-component developer of the present disclosure will be specifically described. First, various measurement methods and evaluation methods will be described.

[0131] 1. Measurement methods, evaluation methods <Measurement of the glass transition temperature of the amorphous polyester resin> Using a differential scanning calorimeter (manufactured by Hitachi High-Tech Science Corporation, model: DSC220), in accordance with JIS (Japanese Industrial Standard) K7121-1987, 1 g of the sample to be measured was heated at a heating rate of 10°C / min to measure the DSC curve. In the obtained DSC curve, the temperature of the intersection of the straight line obtained by extending the baseline on the high-temperature side of the endothermic peak corresponding to the glass transition to the low-temperature side and the tangent line drawn at the point where the gradient becomes maximum with respect to the curve from the rising part of the peak to the apex was defined as the glass transition temperature Tg.

[0132] <Measurement of the ratio of the endothermic amounts of the 1st Run and the 2nd Run in DSC> Using a differential scanning calorimeter (manufactured by Hitachi High-Tech Science Corporation, model: DSC220), first, in order to eliminate the influence of endothermic peaks due to enthalpy relaxation, 1 g of the sample to be measured was heated at a heating rate of 10 ° C / min to a temperature (60 ° C in this case) exceeding the Tg of the binder resin (main resin) and held for 5 minutes, then cooled to 30 ° C at a cooling rate of 10 ° C per minute and held at 30 ° C for 1 minute. Then, as the 1st RUN, the sample was heated to 150 ° C at a heating rate of 10 ° C per minute and the endothermic heat E1 derived from the crystalline polyester resin was measured. Again, the sample was cooled to 30 ° C at a cooling rate of 10 ° C per minute and held at 30 ° C for 1 minute, and then, as the 2nd RUN, the sample was heated to 150 ° C at a heating rate of 10 ° C per minute and the endothermic heat E2 derived from the crystalline polyester resin was measured.

[0133] <Measurement of Softening Temperature of Amorphous Polyester Resin and Crystalline Polyester Resin> Using a flow characteristic evaluation device (Shimadzu Corporation, Flow Tester, Model: CFT-100C), 1 g of the sample to be measured was heated at a temperature increase rate of 6°C / min while applying a load of 20 kgf / cm 2 (9.8×10 5 The sample was allowed to flow out of the die (nozzle diameter 1 mm, length 1 mm) at a pressure of 1 Pa. The temperature at which half of the sample had flowed out was taken as the softening temperature Tm [°C].

[0134] <Measurement of melting point of crystalline polyester resin> Using a differential scanning calorimeter (manufactured by Hitachi High-Tech Science Corporation, model: DSC210), the sample was heated to 200°C, then cooled to 0°C at a rate of 10°C / min, and then heated at a rate of 10°C / min to measure the changes in heat absorption and heat generation. A graph of "heat absorption and heat generation amount" versus "temperature" was plotted, and the temperature corresponding to the maximum peak of the heat absorption and heat generation amount was recorded as the melting point Tmp [°C].

[0135] <Measurement of acid value and hydroxyl value of polyester resin> The acid value and hydroxyl value of the polyester resin were values ​​measured according to the method specified in JIS K0070 (1992 edition). If the sample contained solvent-insoluble matter due to crosslinking, the sample was melt-kneaded according to the following method before use. Mixing equipment: Labo Plastomill manufactured by Toyo Seiki Co., Ltd., model: 4M150 Mixing conditions: 130°C, 70 rpm, 30 minutes

[0136] <Measurement of peak top molecular weight> The peak top molecular weight Mp of the binder resin and the toner was measured by gel permeation chromatography (GPC) under the following conditions. For the measurement of the molecular weight, the polyester resin was dissolved in tetrahydrofuran (THF) and the insoluble matter was filtered off with a glass filter, and the solution was used for measurement. The peak top molecular weight refers to the molecular weight showing the maximum peak height in the chromatogram obtained by GPC measurement. Equipment: Tosoh Corporation HLC-8120 Column: 2 TSK GEL GMH6 (Tosoh Corporation) ·Measurement temperature: 40℃ Sample solution: 0.25% by mass THF solution ·Solution injection volume: 100μl -Detection device: Refractive index detector Standard material: 12 types of standard polystyrene (TSKstandard POLYSTYRENE) manufactured by Tosoh Corporation (molecular weight: 500, 1050, 2800, 5970, 9100, 18100, 37900, 96400, 190000, 355000, 1090000, 2890000)

[0137] <Calculation of SP value of amorphous polyester resin and crystalline polyester resin> The SP values ​​of the amorphous polyester resin and the crystalline polyester resin were calculated by the method proposed by Fedors et al. and described in "POLYMER ENGINEERING AND SCIENCE, FEBRUARY, 1974, Vol. 14, No. 2, ROBERT F. FEDORS. (pp. 147-154)".

[0138] <Measurement of the volume average particle size of toner> 20 mg of toner and 1 mL of sodium alkyl ether sulfate were added to 50 mL of electrolyte (manufactured by Beckman Coulter, Inc., product name: ISOTON-II), and the mixture was dispersed for 3 minutes at a frequency of 20 kHz using an ultrasonic disperser (manufactured by AS ONE Corporation, model: tabletop dual-frequency ultrasonic cleaner VS-D100) to prepare a dispersion for measurement.

[0139] The toner volume particle size distribution of the obtained dispersion for measurement was measured using a particle size distribution measuring device (Model: Multisizer3, manufactured by Beckman Coulter, Inc.) under the conditions of aperture diameter: 100 μm, number of particles measured: 50,000 counts. The volume average particle diameter [μm] was calculated from this volume particle size distribution.

[0140] <Measurement of particle size of oil-treated silica particles> The average primary particle diameter of the oil-treated silica particles was measured twice using a dynamic light scattering particle size distribution analyzer (manufactured by Nikkiso Co., Ltd., model: Nanotrac wave series), and the average value was taken as the average primary particle diameter [μm] of the oil-treated silica particles.

[0141] The measurement conditions were as follows: measurement time 30 seconds, sample particle refractive index 1.49, dispersion medium water, dispersion medium refractive index 1.33. Using the measurement results of the volumetric particle size distribution of the oil-treated silica particles, the particle diameter at which the cumulative volume from the small particle diameter side in the cumulative volume distribution becomes 50% was calculated as the average primary particle diameter [μm].

[0142] <Measurement of the amount of free oil (amount of free carbon) in oil-treated silica particles> 0.7 g of oil-treated silica particles were placed in a cylindrical filter paper with a diameter of 28 mm, and the free silicone oil on the oil-treated silica particles was extracted using a Soxhlet extraction apparatus (manufactured by BUCHI, model: B-811) under the following conditions: extraction solvent: hexane, extraction time: 60 minutes, rinse time: 30 minutes, and the amount of free carbon (free oil amount) was measured.

[0143] The carbon content of the oil-treated silica particles before extraction was measured using an elemental analyzer (model: SUMIGRAPH NX-22F, manufactured by Sumika Chemical Analysis Center, Ltd.) The ratio of the carbon content of the oil-treated silica particles after extraction to the carbon content of the oil-treated silica particles before extraction was calculated as a percentage, and the amount of carbon lost during the extraction process was taken as the free carbon content [%].

[0144] <Measurement of the amount of free fatty acid in fatty acid metal salt particles> The amount of free fatty acids (proportion of free fatty acids) in fatty acid metal salt particles was determined by precisely weighing 1 g of fatty acid metal salt particles, dissolving them in a 1:1 mixture of ethanol and ethyl ether, and neutralizing titrating them with an aqueous potassium hydroxide solution using phenolphthalein as an indicator.

[0145] <Calculation of exposed area of ​​carrier core material (ferrite core material)> The ratio of the area of ​​the carrier core exposed on the carrier surface (core exposed area ratio) can be determined by observing an electron image using a scanning electron microscope (SEM) and subsequent image processing.

[0146] The area ratio of the exposed part of the carrier core material (part derived from metal oxide) is calculated from image processing of the image mainly visualized by secondary backscattered electrons at an accelerating voltage of 1.0 kV. Specifically, the carrier particles were fixed in a single layer with carbon tape on a specimen stage for electron microscope observation, and after a flashing operation was performed without platinum deposition, observation was performed using a scanning electron microscope (Hitachi, Ltd., model: S-4800) under the following measurement conditions. SignalName=SE(U,LA80) AcceleratingVoltage=2000Volt EmissionCurrent=10000nA Working Distance = 6000 μm LensMode=High Condenser1=5 ScanSpeed=Slow4(40 seconds) Magnification=600 DataSize=1280×960 ColorMode=Grayscale

[0147] The projection image of the carrier by the secondary reflected electrons was obtained by adjusting the brightness to 'contrast 5, brightness -5' on the control software of the scanning electron microscope "S-4800", the capture speed / accumulation number to 'Slow 4 for 40 seconds', and the image size to 1280 x 960 pixels as an 8-bit 256-level grayscale image (see example in Figure 4). From the scale on the image, the length of 1 pixel is 0.1667 μm, and the area of ​​1 pixel is 0.0278 μm. 2 It becomes.

[0148] Next, the core material exposed area ratio [area %] was calculated for 50 carrier particles using the projection image obtained by the secondary backscattered electrons. The method for selecting 50 carrier particles to be analyzed will be described in detail later. The core material exposed area ratio was calculated using the image processing software "Image-Pro Plus5.1J" (Media Cybernetics). First, since the text portion at the bottom of the image in Figure 4 is not necessary for image processing, this portion was deleted and the image was cropped to a size of 1280 x 895 pixels (see Figure 5).

[0149] Next, the carrier particle portion was extracted and the size of the extracted carrier particle portion was counted. Specifically, first, the carrier particles were separated from the background portion in order to extract the carrier particles to be analyzed. "Measurement" - "Count / Size" was selected in "Image-Pro Plus5.1J." In "Count / Size," "Brightness Range Selection" was set to a brightness range of 50 to 255, and the low-brightness carbon tape portion that was captured in the background was excluded, and the carrier particles were extracted (see Figure 6).

[0150] When carrier particles are fixed by a method other than carbon tape, the background may not necessarily be a low-luminance area, or may have the same luminance as the carrier particles in some areas. However, the boundaries between the carrier particles and the background can be easily distinguished from the projection image by the secondary backscattered electrons. When extracting, in the extraction options of "Count / Size", "4-connected" was selected, "Smoothness 5" was entered, and "Fill holes" was checked, and particles located on all boundaries (outer peripheries) of the image and particles overlapping with other particles were excluded from the calculation. One particle was selected from the extracted particle group, and the area (number of pixels) of the part originating from that particle was calculated.

[0151] Next, in "Image-Pro Plus5.1J" "Count / Size" "Brightness Range Selection", the brightness range was set to 140 to 255, and high brightness areas on the carrier particles were extracted (see Figure 7). The area selection range was set to a minimum of 10 pixels and a maximum of 10,000 pixels. Then, for the carrier particles selected earlier, the exposed area of ​​the core material on their surface (number of pixels) was calculated.

[0152] Next, the same process was performed on each particle in the extracted particle group until the number of selected carrier particles reached 50. If the number of particles in one field of view was less than 50, the same operation was repeated on the projected images of carrier particles in another field of view.

[0153] By the above procedure, the average ratio of the total area of ​​exposed core material on the carrier particles to the total projected area of ​​the carrier was determined, and this was defined as the ratio of exposed core material area on the carrier surface.

[0154] <Measurement of adhesion strength of external additives> The adhesion strength of the external additive to the toner particles was measured by the following procedure.

[0155] First, a toner sample obtained by carrying out the external additive removal treatments shown in (1) to (6) below was designated as "Sample 1," and a toner sample before carrying out the external additive removal treatments below was designated as "Sample 0." (1) 2.0 g of toner is added to 40 ml of a 0.2% by mass aqueous solution of Triton (polyoxyethylene octylphenyl ether), and the mixture is stirred for 1 minute. (2) The above aqueous solution is irradiated with ultrasonic waves using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho Co., Ltd., model: US-300T) (output: 40 μA, 4 minutes). (3) The aqueous solution after the ultrasonic irradiation is left to stand for 3 hours, and the toner and the liberated external additives are separated. (4) After removing the supernatant, add approximately 50 ml of pure water to the precipitate and stir for 5 minutes. (5) The mixture is subjected to suction filtration using a membrane filter having a pore size of 1 μm (manufactured by Advantec Co., Ltd.). (6) The toner remaining on the filter is vacuum dried overnight.

[0156] Next, the intensity of specific elements in the external additives was analyzed for 1 g of each of "Sample 0" and "Sample 1" using a fluorescent X-ray analyzer (Rigaku Corporation, model: ZSX Primus II), and the adhesion strength [%] was calculated using the following formula (1). The specific elements are "Si" for silica, "Zn" for fatty acid zinc, and "Mg" for fatty acid magnesium. Adhesion strength = (strength for sample 1) / (strength for sample 0) × 100 (1)

[0157] <Evaluation of fog value> The toners of the examples and comparative examples were filled into a color multifunction printer (manufactured by Sharp Corporation, model: BP-20C25) as an evaluation machine, and the evaluation machine was operated in an environmental test room under a low humidity environment (temperature 25°C, relative humidity 5%) and a high humidity environment (temperature 25°C, relative humidity 80%) to measure the fog values ​​under the high humidity environment and the low humidity environment.

[0158] To measure the fog value, an image was printed on the A4 paper in which 1% of the printable area was filled with cyan toner, and a color difference meter (manufactured by Nippon Denshoku Industries Co., Ltd., model: ZE6000) was used to measure the brightness of specific areas that were not filled with the image. The difference between this and the brightness measured in advance before printing was calculated, and this was used as the fog value.

[0159] In the evaluation of fog in the examples and comparative examples, the fog value of the first sheet after printing was measured first. Next, 9998 sheets were printed on A4 paper at a printing rate of 1% (printing an image in which 1% of the printable area of ​​A4 paper was filled with cyan toner), and then the fog value of the 10,000th sheet was measured. Next, the fog value was evaluated according to the following criteria. The specified value of the fog value is a value determined based on the evaluation machine and the evaluation content.

[0160] ◎ (Excellent): The measured value is 80% or less of the specified fogging value. ◯ (Good): The measured value is more than 80% but not more than 90% of the specified fog value. △ (Fair): The measured value is more than 90% and 100% or less of the specified fog value. × (Fail): The measured value is more than 100% of the specified fogging value.

[0161] For example, in Example 1 described later, the measurement value for the first sheet in a low humidity environment was 0.98, and the specified value was set to 1.5, so the measurement value was 65% of the specified value and was evaluated as "Excellent".

[0162] 2. Example of manufacturing two-component developer (1) Preparation of amorphous polyester resin and crystalline polyester resin for toner particles <Preparation of amorphous polyester resin A> In a reaction vessel, 440g (2.7 mol) of terephthalic acid, 235g (1.4 mol) of isophthalic acid, 7g (0.05 mol) of adipic acid, 554g (8.9 mol) of ethylene glycol, and 0.5g of tetrabutoxy titanate as a polymerization catalyst were placed, and the mixture was reacted for 5 hours at 210°C under a nitrogen stream while distilling off the water and ethylene glycol produced, and then reacted for 1 hour under a reduced pressure of 5mmHg to 20mmHg. Next, 103g (0.54 mol) of trimellitic anhydride was added, and the mixture was reacted for 1 hour under normal pressure, and then reacted under a reduced pressure of 20 to 40mmHg, and the resin was taken out at a predetermined softening point. The amount of ethylene glycol recovered was 219g (3.5 mol). The obtained resin was cooled to room temperature and then pulverized into particles. This was designated as amorphous polyester resin A. The amorphous polyester resin A had a Tg of 56° C., a Tm of 135° C., a peak top molecular weight Mp of 5,000, an SP value of 11.0, an acid value of 37 mgKOH / g, and a hydroxyl value of 50 mgKOH / g.

[0163] <Preparation of Crystalline Polyester Resin C1> In a reaction vessel, 132g (1.12 mol) of 1,6-hexanediol, 230g (1.0 mol) of 1,10-decanedicarboxylic acid, and 3g of tetrabutoxy titanate as a polymerization catalyst were placed, and the mixture was reacted for 5 hours at 210°C under normal pressure while distilling off the water produced. The reaction was then continued under reduced pressure of 5mmHg to 20mmHg, and the resin was taken out when the acid value became 2mgKOH / g or less. The resin obtained was cooled to room temperature and then pulverized into particles. This was used as crystalline polyester resin C. The crystalline polyester resin C1 had a Tmp of 80°C, a Tm of 88°C, a Tm / Tmp of 1.1, a peak top molecular weight Mp of 30,000, a SP value of 9.5, an acid value of 1mgKOH / g, and a hydroxyl value of 10mgKOH / g.

[0164] <Preparation of Crystalline Polyester Resin C2> In a reaction vessel, 132g (1.12 mol) of 1,6-hexanediol, 343g (1.0 mol) of 1,18-octadecanedicarboxylic acid, and 3g of tetrabutoxy titanate as a polymerization catalyst were placed, and the mixture was reacted for 5 hours at 210°C under normal pressure while distilling off the water produced. The reaction was then continued under reduced pressure of 5mmHg to 20mmHg, and the resin was taken out when the acid value became 2mgKOH / g or less. The resin obtained was cooled to room temperature, and then pulverized to form particles, which was used as crystalline polyester resin C2. The crystalline polyester resin C2 had a Tmp of 75°C, a Tm of 90°C, a Tm / Tmp of 1.2, a peak top molecular weight Mp of 25,000, a SP value of 9.0, an acid value of 1mgKOH / g, and a hydroxyl value of 5mgKOH / g.

[0165] <Preparation of Crystalline Polyester Resin C3> In a reaction vessel, 118g (1.00 mol) of 1,6-hexanediol, 343g (1.0 mol) of 1,18-octadecanedicarboxylic acid, and 3g of tetrabutoxy titanate as a polymerization catalyst were placed, and the mixture was reacted for 5 hours at 210°C under normal pressure while distilling off the water produced. The reaction was then continued under reduced pressure of 5mmHg to 20mmHg, and the resin was taken out when the acid value became 2mgKOH / g or less. The resin obtained was cooled to room temperature, and then pulverized to form particles, which was used as crystalline polyester resin C3. The crystalline polyester resin C3 had a Tmp of 72°C, a Tm of 90°C, a Tm / Tmp of 1.3, a peak top molecular weight Mp of 25,000, a SP value of 9.9, an acid value of 0mgKOH / g, and a hydroxyl value of 3mgKOH / g.

[0166] (2) Preparation of oil-treated silica particles <Preparation of oil-treated silica particles SiP1> Fumed silica particles with an average primary particle size of 40 nm, produced by burning silicon tetrachloride in an oxyhydrogen flame (flame hydrolysis method), were placed in a reaction vessel. A solution of 20 parts by mass of dimethyl silicone oil diluted with 100 parts by mass of hexane was sprayed onto 100 parts by mass of the silica particles under a nitrogen atmosphere. The mixture was then stirred and dried for 60 minutes at 250°C under a nitrogen atmosphere to obtain oil-treated silica particles SiP1. The particle size of the oil-treated silica particles SiP1 was 40 nm, and the free oil content was 4.5%.

[0167] <Preparation of oil-treated silica particles SiP2-5> Oil-treated silica particles SiP2 to 5 were prepared in the same manner as in the above "Preparation of oil-treated silica particles SiP1" ​​except that the amount of silicon tetrachloride supplied was increased or decreased to control the fumed silica particles to have the desired particle size. The physical properties of these particles are shown in Table 1 below.

[0168] <Preparation of oil-treated silica particles SiP6-9> The amount of dimethyl silicone oil and the drying temperature were adjusted to control the amount of free oil to the desired amount, and the same procedure as in "Preparation of oil-treated silica particles SiP1" ​​was followed to prepare oil-treated silica particles SiP6 to 9. Their physical properties are shown in Table 1 below.

[0169] Table 1 below shows the physical properties of the oil-treated silica particles SiP1 to SiP9.

[0170] [Table 1]

[0171] (3) Preparation of fatty acid metal salt particles <Preparation of fatty acid metal salt particles FM1> 1422 parts by mass of stearic acid was added to 10,000 parts by mass of ethanol and mixed at a liquid temperature of 75°C, and then 507 parts by mass of zinc hydroxide was added little by little, and the mixture was stirred and mixed for 1 hour after the end of the addition. The liquid was then cooled to a temperature of 20°C, and the product was filtered to remove the ethanol and reaction residue, and a solid was extracted. The extracted solid was dried at 150°C for 3 hours using a heated vacuum dryer. The solid was removed from the dryer and allowed to cool, and then the obtained zinc stearate solid was coarsely pulverized using a power mill (manufactured by Dalton Co., Ltd., model: P-3) with a φ2 mm screen to obtain a coarsely pulverized product.

[0172] The obtained coarsely ground material was finely ground using a jet mill (manufactured by Nippon Pneumatic Mfg. Co., Ltd., model: IDS-2) to obtain a finely ground material, which was then classified using an elbow jet classifier (manufactured by Nippon Steel Mining Co., Ltd., model: EJ-LABO) to obtain fatty acid metal salt particles FM1, which are zinc stearate particles. The particle size of the fatty acid metal salt particles (zinc stearate) FM1 was 0.7 μm, and the free fatty acid content was 0.1%.

[0173] <Preparation of fatty acid metal salt particles FM2-5> Fatty acid metal salt particles FM2 to FM5 were prepared in the same manner as in the above "Preparation of fatty acid metal salt particles FM1" except that the fine pulverization conditions and classification conditions were changed. The physical properties of these particles are shown in Table 2 below.

[0174] <Preparation of fatty acid metal salt particles FM6> Fatty acid metal salt particles FM6 were prepared in the same manner as in "Preparation of fatty acid metal salt particles FM1" above, except that 507 parts by mass of zinc hydroxide was changed to 293 parts by mass of magnesium hydroxide, and the fine pulverization conditions and classification conditions were changed. The fatty acid metal salt particles (magnesium stearate) FM6 had a particle size of 1.0 μm and a free fatty acid content of 0.7%.

[0175] <Preparation of fatty acid metal salt particles FM7> Fatty acid metal salt particles FM7 were prepared in the same manner as in "Preparation of fatty acid metal salt particles FM1" above, except that 1,422 parts by mass of stearic acid was changed to 1,005 parts by mass of lauric acid, and the fine pulverization conditions and classification conditions were changed. The particle size of fatty acid metal salt particles (zinc laurate) FM7 was 1.0 μm, and the free fatty acid content was 0.8%.

[0176] <Preparation of fatty acid metal salt particles FM8> Fatty acid metal salt particles FM8 were prepared in the same manner as in "Preparation of fatty acid metal salt particles FM1" above, except that 1,422 parts by mass of stearic acid was changed to 1,144 parts by mass of myristic acid, and the fine pulverization conditions and classification conditions were changed. The particle size of fatty acid metal salt particles (zinc myristic acid) FM8 was 1.0 μm, and the free fatty acid content was 0.6%.

[0177] Table 2 below shows the physical properties of the fatty acid metal salt particles FM1 to FM8.

[0178] [Table 2]

[0179] (4) Carrier manufacturing First, the following five types of coating resins were prepared to form the resin coating layer. ·Straight silicone resin Coating resin 1: KR-240 (product name, manufactured by Shin-Etsu Chemical Co., Ltd., Mw = 5.0 × 10 2 ) Coating resin 2: KR-251 (product name, manufactured by Shin-Etsu Chemical Co., Ltd., Mw = 5.0 × 10 5 ) Coating resin 3: KR-350 (product name, manufactured by Shin-Etsu Chemical Co., Ltd., Mw = 4.0 × 10 3 ) Acrylic resin Coating resin 4: LR-1065 (product name, manufactured by Mitsubishi Chemical Corporation) Acrylic modified silicone resin Coating resin 5: KR-9706 (product name, manufactured by Shin-Etsu Chemical Co., Ltd.)

[0180] <Preparation of resin-coated carrier Car1> 0.75 parts by mass of "coating resin 1" and 0.75 parts by mass of "coating resin 2" were dissolved in 12 parts by mass of toluene, and 0.0575 parts by mass of conductive particles (product name: VULCAN XC-72, manufactured by Cabot Corporation) and 0.0425 parts by mass of coupling agent (product name: AY43-059, manufactured by Toray Dow Corning Co., Ltd.) were dispersed therein to prepare a coating resin liquid. The surface of 100 parts by mass of ferrite core material with a volume average particle size of 40 μm was coated with 13.6 parts by mass of the coating resin liquid by the immersion method. After that, a curing process was performed at a curing temperature of 200°C and a curing time of 1 hour, and the resin-coated carrier was produced by passing it through a sieve with an opening of 150 μm. The core material exposed area ratio on the carrier surface was 15%.

[0181] <Preparation of resin-coated carriers Car2 to 7> Resin-coated carriers Car2 to 7 were prepared in the same manner as in "Preparation of resin-coated carrier Car1" above, except that the types and amounts of coating resins were changed as shown in Table 3 below.

[0182] The physical properties of the resin-coated carriers Car1 to 7 are shown in Table 3 below.

[0183] [Table 3]

[0184] (5) Manufacture of toner and two-component developers [Example 1] -Toner particle production process- The following toner materials were used to prepare the toner particles (toner cores). Binder resin: Amorphous polyester resin A 80% by mass Crystalline resin: 8% by mass of crystalline polyester resin C1 Colorant: CI Pigment Blue 15:3 (DIC Corporation) 6% by weight Release agent: WEP3 (product name, manufactured by NOF Corporation) 5% by mass Charge control agent: Salicylic acid compound (product name: Bontro E84, Orient Chemical Industries Co., Ltd.) 1% by mass

[0185] The above materials were premixed for 5 minutes using a Henschel mixer (manufactured by Nippon Coke & Engineering Co., Ltd., model: FM20C), and then melt-kneaded using an open-roll type continuous kneader (manufactured by Nippon Coke & Engineering Co., Ltd., model: MOS320-1800). The open-roll setting conditions were a heating roll supply side temperature of 130°C, a discharge side temperature of 100°C, a cooling roll supply side temperature of 40°C, and a discharge side temperature of 25°C. The heating roll and the cooling roll both had a diameter of 320 mm and an effective length of 1550 mm, and the gap between the rolls on the supply side and the discharge side was both 0.3 mm. The rotation speed of the heating roll was 75 rpm, the rotation speed of the cooling roll was 65 rpm, and the supply amount of the toner material was 5.0 kg / h.

[0186] Next, the resulting molten kneaded product was cooled with a cooling belt, and then coarsely pulverized with a speed mill having a φ2 mm screen.

[0187] The resulting coarsely pulverized material was then finely pulverized using a jet pulverizer (manufactured by Nippon Pneumatic Mfg. Co., Ltd., model: IDS-2).

[0188] The resulting finely pulverized material was then classified using an elbow jet classifier (Model: EJ-LABO, manufactured by Nittetsu Mining Co., Ltd.) to obtain toner particles. The average primary particle diameter of the obtained toner particles was 6.7 μm.

[0189] -External addition process- To 100 parts by mass of the obtained toner particles, 0.5 parts by mass of titanium oxide particles (product name: JMT-150, manufactured by Teika Corporation, average primary particle diameter 15 nm) and 1.0 parts by mass of oil-treated silica particles "SiP1" ​​were added, and the mixture was stirred for 2 minutes with a Henschel mixer (manufactured by Nippon Coke & Engineering Co., Ltd., model: FM20C) with the tip speed of the stirring blade set to 40 m / sec, and then 0.2 parts by mass of fatty acid metal salt particles "FM1" were added, and the tip speed of the Henschel mixer was set to 40 m / sec and stirred for 2 minutes to obtain a toner. In the obtained toner, the adhesion strength of the oil-treated silica particles was 55%, and the adhesion strength of the fatty acid metal salt particles was 15%.

[0190] -Developer manufacturing process- The obtained toner (toner after the external addition step) and the resin-coated carrier Car1 were mixed so that the toner concentration relative to the total amount of the two-component developer was 7%, to obtain a two-component developer with a toner concentration of 7%.

[0191] [Examples 2 to 21, Comparative Examples 1 to 9] A two-component developer was obtained in the same manner as in Example 1, except that the types and amounts of the "oil-treated silica particles" and "fatty acid metal salt particles" were changed as shown in Table 4 below, and the type of the "carrier" was changed as shown in Table 5 below.

[0192] [Table 4]

[0193] [Table 5]

[0194] [Table 6]

[0195] Table 6 shows the evaluation results of the examples and comparative examples. As is clear from the evaluation results, the two-component developer of Examples 1 to 21, which is a toner having an external additive attached to the surface of the toner particles and a carrier, the toner particles contain an amorphous polyester resin and a crystalline polyester resin, the external additive contains fatty acid metal salt particles and silica particles surface-treated with silicone oil, the free oil amount of the silica particles is 3% to 6%, the particle diameter of the fatty acid metal salt particles is 0.5 μm to 1.5 μm, and the carrier is a ferrite core material having a straight silicone resin coating layer formed on at least a part of the surface, can suppress the occurrence of fogging throughout the product life in both low humidity and high humidity environments. In other words, the charge rise was good throughout the product life.

[0196] In contrast, Comparative Examples 1 to 9, which did not satisfy these requirements, were inferior to the Examples in the evaluation of fogging throughout the product life.

[0197] It can be seen that Examples 1 and 2, in which the ratio of endothermic heat amounts E2 / E1 between the 1st run and the 2nd run in the DSC is 90% or more, have an optimized compatibility between the crystalline polyester resin and the amorphous polyester resin, which is the binder resin, and therefore have superior fogging evaluation results in both low-humidity and high-humidity environments compared to Example 3, in which E2 / E1 is outside the above range.

[0198] It can be seen that Examples 1, 4 and 5, in which the particle diameter of the oil-treated silica particles is 10 nm or more and 100 nm or less, are superior in the evaluation of fogging throughout the product life than Examples 6 and 7, in which the particle diameter is outside the above range.

[0199] Also, Examples 1, 4 and 5, in which the adhesion strength of the oil-treated silica particles to the toner particles is 45% or more and 75% or less, are superior in the evaluation of fogging throughout the product life than Examples 6 and 7, in which the adhesion strength is outside the above range.

[0200] It is clear that Example 1, in which the adhesion strength of the fatty acid metal salt particles to the toner particles is 25% or less, is superior in the evaluation of fogging throughout the product life than Examples 11 and 15, in which the adhesion strength is outside the above range.

[0201] It can be seen that Example 1, in which the carbon number of the fatty acid in the fatty acid metal salt particles is 16 or more, is superior in the evaluation of fogging throughout the product life than Examples 13 and 14, in which the carbon number of the fatty acid is outside the above range.

[0202] It is clear that Example 1, in which the proportion of free fatty acids in the fatty acid metal salt particles is 0.2% or less, is superior in the evaluation of fogging throughout the product life span to Examples 12 to 14, in which the proportion of free fatty acids is outside the above range.

[0203] If the particle diameter of the oil-treated silica particles is Dp and the particle diameter of the fatty acid metal salt particles is Df, it can be seen that Examples 1 and 5, in which Dp / Df is less than 0.15, have superior evaluations of fogging throughout the product life than Examples 7 and 15, in which Dp / Df is outside the above range.

[0204] If the content of oil-treated silica particles in the two-component developer is Cp and the content of fatty acid metal salt particles is Cf, it can be seen that Examples 1 and 16, in which Cp / Cf is less than 10, have superior fogging evaluations throughout the product life than Example 17, in which Cp / Cf is outside the above range.

[0205] It can be seen that Examples 1, 18, and 19, in which the area ratio of the exposed ferrite core material on the carrier surface is 5% or more and 20% or less, are able to suppress the occurrence of fogging in low-humidity and high-humidity environments in a balanced manner compared to Examples 20 and 21, in which the ratio is outside the above range.

[0206] The embodiments disclosed herein are illustrative in all respects and are not intended to be limiting. Therefore, the technical scope of the present disclosure is not interpreted solely by the above-described embodiments, but is defined based on the claims. Also, all modifications within the scope and meaning equivalent to the claims are included. [Explanation of symbols]

[0207] 1 Toner 11 Amorphous polyester resin 12 Crystalline polyester resin 12a Compatible part 13 Silica particles surface-treated with silicone oil 13′ Silica particles 13 transferred to the carrier surface 14. Fatty acid metal salt particles 14' Fatty acid metal salt particles migrated to the carrier surface 14 2. Career 21 Ferrite core material 22 Straight silicone resin coating layer

Claims

1. A two-component developer containing a toner having an external additive attached to the surface of the toner particles and a carrier, the toner particles contain an amorphous polyester resin and a crystalline polyester resin, The external additive includes fatty acid metal salt particles and silica particles surface-treated with silicone oil, The silica particles have a free oil content of 3% or more and 6% or less, The particle diameter of the fatty acid metal salt particles is 0.5 μm or more and 1.5 μm or less, The two-component developer is characterized in that the carrier is a ferrite core material having a straight silicone resin coating layer formed on at least a part of the surface thereof.

2. The two-component developer according to claim 1 , In the differential scanning calorimetry of the toner, The amount of heat absorbed by the crystalline polyester resin in the first run in which the temperature is increased from 30° C. to 150° C. at a temperature increase rate of 10° C. per minute is defined as E1. After the first run, the material is cooled to 30° C. at a cooling rate of 10° C. per minute and held for 1 minute. Then, the material is heated again from 30° C. to 150° C. at a heating rate of 10° C. per minute in the second run. The amount of heat absorbed by the crystalline polyester resin in the second run is defined as E2. A two-component developer, wherein the ratio E2 / E1 of the amounts of heat absorption is 90% or more.

3. The two-component developer according to claim 1 or 2, A two-component developer, wherein a ratio of an area of ​​the portion where the ferrite core material is exposed on the surface of the carrier is 5% or more and 20% or less.

4. The two-component developer according to claim 1 or 2, The two-component developer, wherein the silica particles have a particle diameter of 10 nm or more and 100 nm or less.

5. The two-component developer according to claim 1 or 2, an adhesion strength of the silica particles to the toner particles is 45% or more and 75% or less; 2. A two-component developer, wherein the adhesive strength of the fatty acid metal salt particles to the toner particles is 25% or less.

6. The two-component developer according to claim 1 or 2, The two-component developer is characterized in that the fatty acid of the fatty acid metal salt particles has 12 or more carbon atoms.

7. The two-component developer according to claim 1 or 2, A two-component developer, wherein the fatty acid metal salt particles have a free fatty acid content of 0.2% or less.

8. The two-component developer according to claim 1 or 2, The two-component developer is characterized in that, when the particle diameter of the silica particles is Dp and the particle diameter of the fatty acid metal salt particles is Df, Dp / Df is less than 0.

15.

9. The two-component developer according to claim 1 or 2, The two-component developer, wherein Cp / Cf is less than 10, where Cp is the content of the silica particles in the two-component developer and Cf is the content of the fatty acid metal salt particles.

Citation Information

Patent Citations

  • Toner

    JP2011047988A